2015
DOI: 10.1007/s00705-015-2472-5
|View full text |Cite
|
Sign up to set email alerts
|

Full-genome sequence of a novel myovirus, GF-2, infecting Edwardsiella tarda: comparison with other Edwardsiella myoviral genomes

Abstract: Edwardsiellosis, which is caused by Edwardsiella tarda, a Gram-negative bacterium, is one of the most serious infectious diseases in both marine and freshwater fish farms worldwide. Previously, we reported the complete genome sequences of three E. tarda-lytic bacteriophages (two podoviruses and a myovirus), which were isolated from fish tissues and fish-rearing seawater. Further genomic information regarding E. tarda phages is important for understanding phage-host interactions as well as for applications of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…The five exceptional newly sequenced phages, IME-EC2 ( Escherichia ; Accession No. KF591601; Hua et al , 2014), Ss1 ( Cronobacter ; KM058087; Endersen et al , 2014), CVT22 (Citrobacter; KP774835; Tikhe et al , 2015), SEN34 ( Salmonella , KT630649), and GF-2 ( Edwardsiella ; AP014629; Yasuike et al , 2015) are founding phages of three new lytic and two new temperate clusters (our unpublished observations). The small number of new clusters generated by the many recently sequenced genomes supports the notion that, at least for the best-studied genera of this bacterial family, Escherichia and Salmonella, most of the common tailed phage types that infect them have been discovered.…”
Section: Introductionmentioning
confidence: 77%
“…The five exceptional newly sequenced phages, IME-EC2 ( Escherichia ; Accession No. KF591601; Hua et al , 2014), Ss1 ( Cronobacter ; KM058087; Endersen et al , 2014), CVT22 (Citrobacter; KP774835; Tikhe et al , 2015), SEN34 ( Salmonella , KT630649), and GF-2 ( Edwardsiella ; AP014629; Yasuike et al , 2015) are founding phages of three new lytic and two new temperate clusters (our unpublished observations). The small number of new clusters generated by the many recently sequenced genomes supports the notion that, at least for the best-studied genera of this bacterial family, Escherichia and Salmonella, most of the common tailed phage types that infect them have been discovered.…”
Section: Introductionmentioning
confidence: 77%
“…Measurements made on the obtained TEM pictures, revealed that the Edno5 bacteriophage has an icosahedral (isometric) capsid of 68.1 ± 3.5 nm equipped with a long rigid tail of 74.5 ± 4.1 × 18.2 ± 2.3 nm ( n = 14). Endo5 virions resemble those of the E. tarda myoviruses GF-2 and MSW-3 since they were about 61 and 60 nm in capsid diameter and 81.6 and 80 nm in tail length, respectively (Kawato and Nakai, 2012; Yasuike et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Edwardsiella is also a member of Enterobacteriaceae family, thus comparing these already studied systems to E. anguillarum- Edno5 phage system, reveals potentially conserved regulatory mechanisms. Specifically, gene homologs of cI , cro , and cII that are present in bacteriophage lambda are also found in the genome of Edno5 and relative E. tarda phage GF-2 (Yasuike et al, 2015). The lysogenic pathway can be interrupted by the expression of the cro gene (gene 53 in Edno5) which turns off early gene transcription during the lytic cycle.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequence of the GF-2 phage was present in 90% (27/30) of the total genomes analyzed and in all of the European genomes. Historically, Yasuike et al described for the first time the GF-2 phage, a myovirus lytic bacteriophage in 2015 [22]. It was isolated from a cultured Japanese flounder that succumbed to Edwardsiella tarda , a Gram-negative Enterobacteriaceae that is the most serious pathogen in both marine and freshwater fish farms worldwide.…”
Section: Discussionmentioning
confidence: 99%